Valoración del recurso forestal del campus La María de la Universidad Técnica Estatal de Quevedo ubicado en el cantón Mocache, provincia de Los Ríos - Bravo Pacheco, Jennifer Lisbeth (2022)
Forest resources are the elements that come from forests and are mainly used to satisfy human needs. This research project was carried out with the purpose of assessing the forest resource of the "La María" campus of the Quevedo State Technical University located in the Mocache canton, province of Los Ríos. For the development of the research,